Predictive Effect of Systemic Immune-Inflammation Index Combined With Prognostic Nutrition Index Score on Efficacy and Prognosis of Neoadjuvant Intraperitoneal and Systemic Paclitaxel Combined With Apatinib Conversion Therapy in Gastric Cancer Patients With Positive Peritoneal Lavage Cytology: A Prospective Study - Ding, Ping’an; Yang, Peigang; Sun, Chenyu; Tian, Yuan; Guo, Honghai; Liu, Yang; Li, Yong; Zhao, Qun (Frontiers in Oncology, 2022)
Background: Gastric cancer with only peritoneal lavage cytology (GC-CY1) is a special type of gastric cancer, which is defined as stage IV. The pre-treatment systemic immune-inflammation index (SII) and prognostic nutritional index (PNI) are representative blood indexes of systemic inflammatory response and nutritional status. However, the clinical significance of combined detection of these two indexes is still unclear. This study aims to evaluate the clinical value of the new score system by combining SII and PNI (SII-PNI score) as a predictor of efficacy and prognosis after neoadjuvant intraperitoneal and systemic (NIPS) paclitaxel combined with Apatinib conversion therapy for GC-CY1 patients. Methods: We registered a prospective clinical study involving 36 GC-CY1 patients from April 2018 to August 2019 (NCT03718624). All patients underwent re-laparoscopic exploration after treatment. According to free cancer cells (FCCs) status, these patients were divided into FCCs group and non-FCCs group. The SII-PNI score ranged from 0 to 2 as follows: score of 2, high SII (≥512.1) and low PNI (≤52.9); score of 1, either high SII or low PNI; score of 0, no high SII nor low PNI. Results: All patients underwent re-laparoscopic exploration after 3 cycles of NIPS paclitaxel and Apatinib conversion therapy. Among them, 28 cases (77.78%) were in non-FCCs group, and 8 cases (22.22%) were in FCCs group. The SII-PNI score of non-FCCs patients was significantly lower than that of FCCs patients (p=0.041). The prognosis of patients with high SII-PNI score was significantly worse than that of patients with low SII-PNI score (p<0.001). Multivariate analysis showed that SII-PNI score was an independent prognostic factor for predicting overall survival and progression-free survival (p=0.001, 0.002). Conclusion: Pretreatment SII-PNI score is an important predictor for the efficacy of GC-CY1 patients after NIPS paclitaxel combined with Apatinib conversion therapy, which can help to identify high-risk groups and predict prognosis.